Determinants influencing health-promoting behaviors in individuals at high risks of stroke: a cross-sectional study - Chen, Mengxia; Wang, Mengdi; Qiao, Mengting; Huang, Xiaorong; Li, Dongmei; Yu, Longjuan; Gan, Lifen; Chen, Wenyao; Weng, Yanqiu; Zhang, Jingwen; Yu, Bing; Liu, Jianmin; et al. (Frontiers in Public Health, 2024)
Quit smoking, moderate drinking, exercise, and healthy eating habits are all known to decrease the risk of stroke. As a result, understanding the health behaviors of high risk groups for stroke is crucial. Health behavior is influenced by knowledge, social environment, and health beliefs.However, little research has been done on these relationships. For a better grasp of the relationships mentioned above, consider using the COM-B model (capability, opportunity, and motivation). The purpose of this study was to investigate the variables related to health behavior and to test the mediating effect of health beliefs.The cross-sectional study was carried out at a physical examination center of a tertiary hospital in Shanghai, China. 986 high-risk populations of stroke have been tested using the Health Behavior Scale (HBS-SP), Stroke Knowledge Questionnaire(SKQ), Health Beliefs Questionnaire(HBS) , and Multidimensional Scale of Perceived Social Support (MSPSS). The structural equation modeling was used in this study.The scores for MSPSS, SKQ, HBS, and HBS-SP were 60.64±13.72, 26.60±9.77, 157.71±34.34, and 2.46±0.41, respectively. The revised model fits well (approximate root mean square error=0.042; comparative fit index=0.946). The health behavior was obviously and positively correlated to social Support, stroke knowledge, and health beliefs. Moreover, health belief has a mediating effect on the relation of social support, stroke knowledge, and health behavior.Chinese high risk groups for stroke have a mediate level of health behaviors. Factors associated with health behaviors are knowledge of stroke, health beliefs, and social support. The COM-B-based model can be used to explain the health behavior of individuals at risk of stroke and to guide the formulation of effective health management programs. Keywords the high-risk population of stroke, health behaviors, health beliefs, stroke knowledge, social support * 0.100 ** 0.089 ** 0.107 ** 0.367 ** 0.165 ** 0.235 ** 0.243 ** * 0.500 ** 0.496 ** 0.532 ** 0.480 **